Methodology for the ex-post evaluation of operational programmes co-financed by the ESF - Planas, Jordi [Verfasser]; Garcia, Maribel [Verfasser]; Romani, Claudine [Mitarbeiter]; Bulgarelli, Aviana [Mitarbeiter]; Werner, Heinz [Mitarbeiter]; Blaschke, Dieter [Mitarbeiter]; Lindley, Robert [Mitarbeiter] (My University, 1991)
"The Single European Act refers to the need for economic and social cohesion, and this need inspires the schemes provides by the Community's Structural Funds. The Community invests its own resources from its Funds to this end and, in order to understand better the results of those investments, it accompaties them with the creation of instruments of evaluation. The aim of this is to develop a culture of evaluation which is becoming daily more necessary. The Community's investments, as wel as helping to resolve immediate problems, therefore create the conditions for the improvement of policies in Member States, which should allow progress along the road to the cohesion that is desired. This report stands partly within the framework of reflection on the methods being suggested with a view to the coming together of Member States for the evaluation of programmes co-financed by the E.S.F. In part also it aims to define actual methods and to describe the most appropriate conditions for implementing the ex-post evaluation of these programmes. In this document we also present a comprehensive approach that aims to simplify methodological features associated with the ex-post evaluation envisaged by the regulations of the Funds. With this in mind, we propose actual methods to be used for the ex-post evaluation of this type of programme. In short, this report should be seen as having a dual purpose:(a) to show how to evaluate actual programmes in order to improve public policies;(b) to co-operate in the development of an evaluative approach that would have a certain continuity, at least as far as the creation of a tradition of reflection on and analysis of the schemes developed within the Community's framework." (author's abstract, IAB-Doku) ((en))
Keywords: I 1.4 Berufsbildungsprojekte/Entwicklungsprojekte; L 6.2.3 Evaluation; T 3 Forschungsmethoden; S 4.1.1 Öffentliche Finanzierung; G 1.2 Arbeitsmarkt; G 2.5.4 Qualifizierungs- & Ausbildungskonzepte; I 2.2 Europa; Europäischer Sozialfonds; Wirkungsforschung; Investitionen; Öffentliche Ausgaben; Arbeitsförderung; Berufliche Weiterbildung; Qualifizierung; Umschulung; Quantitative Angaben; Europäische Union